2010
DOI: 10.1016/j.jpainsymman.2010.03.024
|View full text |Cite
|
Sign up to set email alerts
|

Family Caregiver Perspectives on Symptoms and Treatments for Patients Dying From Complications of Cystic Fibrosis

Abstract: Context-Most patients with advanced cystic fibrosis (CF) die from respiratory failure and experience distressing symptoms as lung disease progresses. Little has been reported about symptom management and the continuation of disease-specific treatments near the end of life for patients with CF.Objective-We aimed to describe symptom prevalence, symptom management, and frequency of use of disease-specific treatments for patients dying from complications of CF.Methods-We conducted semistructured interviews about e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 23 publications
(21 reference statements)
0
25
0
2
Order By: Relevance
“…O esforço contínuo é muitas vezes exigido no processo do cuidado, somado a outras responsabilidades do cuidador, como filhos, fatores esses que deterioram a sua saúde. 16 .…”
Section: Discussionunclassified
“…O esforço contínuo é muitas vezes exigido no processo do cuidado, somado a outras responsabilidades do cuidador, como filhos, fatores esses que deterioram a sua saúde. 16 .…”
Section: Discussionunclassified
“…Both showed that cough had a negative impact on global QoL [75]. This is also the case in many respiratory conditions wherein both global QoL and cough specific QoL are affected by cough [64,74,[76][77][78][79][80][81][82]. However, the impact of cough differs even if the change in QoL score is similar.…”
Section: Assessment Of Impactmentioning
confidence: 92%
“…Distressing symptoms such as dyspnea, cough, pain, fatigue, and anxiety are common in people dying from complications of CF (Fig. ) . Achieving effective symptom management necessitates developing an individualized plan involving pharmacologic and non‐pharmacologic therapies, co‐managing discomforts of necessary CF therapies and side effects of medications used to manage symptoms, and educating patients and families about symptoms to anticipate as death approaches.…”
Section: End Of Life Carementioning
confidence: 99%